Habitus Peserta Didik dalam Keputusan Melanjutkan Pendidikan Tinggi di MAS Al-Fathaniyah Kota Serang - Kholillah, Kholillah; Setiawan, Rizki (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
This study aims to understand the habitus of students in the decision to continue higher education at MAS Al-Fathaniyah, Serang City. This study uses a qualitative research method with a phenomenological approach. Data collection techniques are carried out through observation, interviews, and documentation. The researcher uses analysis by coding as a data analysis process. The author's strategy in assessing the accuracy of research results is to use a triangulation strategy. In this study, the informants selected were grade 12 students, teachers, and the Deputy Head of Madrasah for Curriculum (waka curriculum). The results of this study show that students' perceptions and habits of higher education, social and cultural capital in the form of educational habitus, the realm of schools and pesantren as habitus reproductive spaces, structural challenges: economic capital and structural obstacles to higher education, and habitus transformation, efforts to strengthen school motivation and strategies. The results of these findings provide recommendations for schools in strengthening students' educational habits.